2011
DOI: 10.1590/s0034-737x2011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade e composição estrutural de aveia e azevém submetidos a épocas de corte e adubação nitrogenada

Abstract: Yield and structural composition of oat and ryegrass subjected to different periods of cutting and nitrogen fertilizationDairy farming represents an important activity to small farmers, in south-west of Parana State, Brazil. The objective of this study was to evaluate the effect of the harvest period of oat and rye grass pastures, with and without nitrogen fertilization, on dry matter and pasture quality in order to determine the best time to start grazing. The experiment was carried out in Pato Branco, PR, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
9
0
2
Order By: Relevance
“…Longer biomass accumulation periods either in autumn or spring are vital for milk or meat production on pasture because they reduce forage shortages. In addition to sowing grass-legume consortia, other strategies are used ease forage shortages including staggering forage seeding times (Pin, Soares, Possenti, & Ferrazza, 2011) and cutting seasons (Cassol, Piva, Soares, & Assmann, 2015).…”
Section: Acta Scientiarum Animal Sciencesmentioning
confidence: 99%
“…Longer biomass accumulation periods either in autumn or spring are vital for milk or meat production on pasture because they reduce forage shortages. In addition to sowing grass-legume consortia, other strategies are used ease forage shortages including staggering forage seeding times (Pin, Soares, Possenti, & Ferrazza, 2011) and cutting seasons (Cassol, Piva, Soares, & Assmann, 2015).…”
Section: Acta Scientiarum Animal Sciencesmentioning
confidence: 99%
“…Lupatini et al (1998) affirmed that a utilization of 150 kg N ha -1 can result in an increase of up to 122% in the rate of accumulation of pasture dry matter. In addition, according to Cassol et al (2011), the use of nitrogen to produce an increase in dry matter makes it possible to anticipate the entry of grazing animals, promoting better pasture utilization and higher productivity.…”
Section: Resultsmentioning
confidence: 99%
“…There was a higher percentage of oat leaves in the pastures that received nitrogen fertilization, which produced the equivalent of 1015.8 kg DM more oat leaves per hectare than non-fertilized pastures. The higher yield of oat leaves is attributed to the positive effects of nitrogen through greater accumulation of biomass and changes in tiller dynamics, which resulted in a higher proportion of young tillers in the pasture (CAMINHA et al, 2010;CASSOL et al, 2011) and generated a higher proportion of leaves. In addition, according to Pellegrini et al (2010), a high percentage of leaves is also a result of the influence of nitrogen acting in zones of stretching and cell division, causing an increase in the number of cells and favoring the expansion and appearance of leaves.…”
Section: Resultsmentioning
confidence: 99%
“…Phyllochrons may be reduced with N fertilization because it increases the plant growth, resulting in bigger regrowth capacity, given to the plants a fast replacement of leaf area (Lemaire and Chapman, 1996). Cassol et al (2011) observed that with the utilization of nitrogen there was a greater amount of leaves produced by oats in 45 days than in 60 days without its use, noted that if N fertilization was not used in oats (Avena strigosa) and ryegrass (Lollium multiflorum) the plants needed 15 more days to accumulate a similar amount of dry matter than when N fertilization was used. This proves the influence of nitrogen in the production of citocinine, an hormone responsible for the plant growth and that acts activating of the process of cellular division and differentiation (Marschner, 1995).…”
Section: The Importance Of Nitrogen In Pasturesmentioning
confidence: 99%